Globalization, nationalism, and music education in the twenty-first century in Greater China - Ho, Wai-chung (Amsterdam University Press, 2021)
This book will examine the recent development of school music education in Mainland China, Hong Kong, and Taiwan to illustrate how national policies for music in the school curriculum integrate music cultures and non-musical values in the relationship between national cultural identity and globalization. It will examine the ways in which policies for national identity formation and globalization interact to complement and contradict each other in the content of music education in these three Chinese territories. Meanwhile, tensions posed by the complex relationship between cultural diversity and political change have also led to a crisis of national identity in these three localities. The research methods of this book involve an analysis of official approved music textbooks, a survey questionnaire distributed to students attending music education programmes as well as primary and secondary school music teachers, and in-depth interviews with student teachers and schoolteachers in the three territories.